2020
DOI: 10.1007/s00508-020-01786-8
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a telerehabilitation program for patients with Duchenne muscular dystrophy in the COVID-19 pandemic

Abstract: Summary Background Duchenne muscular dystrophy is a genetic disease characterized by gradual loss of motor function, respiratory failure and cardiomyopathy. During the time of the global coronavirus pandemic, maintenance of social distancing and self-isolation might complicate regular multidisciplinary care of patients with Duchenne muscular dystrophy but on the other hand may lead to new medical care telehealth solutions. The aim of the study was to investigate patients’ situation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 25 publications
0
33
0
4
Order By: Relevance
“…In that study, the authors established an online program of rehabilitation based on virtual workshops, videos with exercise instructions with the participation of multidisciplinary team, and/or individual online consultations. The possibility to continue online their rehabilitation was positively received by patients and caregivers, with high level of usage [ 29 ]. By enhancing the engagement of NM patients and by developing a specific model of telerehabilitation for NM care, the goal is to improve the physical and mental health of our patients, decreasing trips to the hospital and amount of pharmacological therapies.…”
Section: Digital Therapeuticsmentioning
confidence: 99%
“…In that study, the authors established an online program of rehabilitation based on virtual workshops, videos with exercise instructions with the participation of multidisciplinary team, and/or individual online consultations. The possibility to continue online their rehabilitation was positively received by patients and caregivers, with high level of usage [ 29 ]. By enhancing the engagement of NM patients and by developing a specific model of telerehabilitation for NM care, the goal is to improve the physical and mental health of our patients, decreasing trips to the hospital and amount of pharmacological therapies.…”
Section: Digital Therapeuticsmentioning
confidence: 99%
“…The most important finding is the fact that the telerehabilitation is acceptable by patients with DMD and caregivers, and can be performed using video techniques as instructions. This fact is especially important during the pandemic period, as our previous study showed, in which almost all patients stopped institutional physical therapy due to the national recommendations of social isolation, and the majority of them continued physical therapy at home [9]. Limited attendance for institutional rehabilitation indicates the urgent need to implement well-designed telerehabilitation programs that meet the specific needs of DMD patients.…”
Section: Discussionmentioning
confidence: 96%
“…It is well documented that rehabilitation with glucocorticosteroid treatment slows down the disease progress; it prolongs ambulation, delays respiratory function deterioration, and decreases the risk of severe scoliosis. Traditional rehabilitation consisting of stretching, positioning, exercises improving strength and endurance, postural re-education, and respiratory management is a key intervention for maintaining and preserving optimal function and participation [9]. Constant direct treatment implemented by physical therapists and occupational therapists should be tailored to the patient's age, individual needs, and stage of disease [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that DMD patients are at risk of severe course of COVID-19 [5] the multidisciplinary healthcare team is seeking the safest way to provide constant care and treatment on the highest possible level. The innovative digital form of physical therapy which is easily available, free of charge and adjustable can support the daily routine of home training in the time of social distancing [6].…”
Section: Introductionmentioning
confidence: 99%